Penerapan Algoritma C4.5 Data Mining Dalam Mengukur Tingkat Kepuasaan Masyarakat Kecamatan Siantar Terhadap Perbaikan Jalan 2019 - Riama Ester Angelina Sihombing; Jaya Tata Hardinata; Zulaini Masruro Nasution (LPPM STIKOM Tunas Bangsa, 2021)
Roads are land transportation infrastructures that are used every day by humans both on the surface of the land, below the surface of the land or above the surface of the water. This means that the road is a very important supporting factor in carrying out daily human life, both roads in village and roads in the city. But not all people of Kabupaten Simalungun , especially Kec. Siantar feel that their roads are worth using, but not a few also feel happy that their roads are being repaired. For this reason, the writer would like to know the level of satisfaction of the people of Kabupaten Simalungun, especially Kec. Siantar towards road improvement in their respective areas that has been carried out by the Dinas Pekerjaan Umum Kabupaten Simalungun. The method that I use is the C4.5 algorithm, also called a decision tree, which uses a tree structure representation, the concept of this decision tree is to collect data, then a decision tree is created which will then produce rules for problem solutions, so that this method can know effectively the level of community satisfaction specifically Kabupaten Simalungun.